Independent Risk Factors for Revision Surgery or Conversion to THA after Hip Arthroscopy: An Analysis of 3, 957 Patients. Issue 7 (21st July 2017) - Kester, Benjamin; Mahure, Siddharth Ashok; Capogna, Brian; Ryan, Michael K.; Wolfson, Theodore; Hamula, Mathew; Rokito, Andrew S.; Youm, Thomas
Objectives: The use of hip arthroscopy for the management of hip pathology has increased dramatically in recent years. Despite evidence demonstrating excellent outcomes, there are some patients that may require revision arthroscopy or conversion to total hip arthroplasty (THA). Data regarding risk factors for poor outcomes after hip arthroscopy is limited. The purpose of this study is to evaluate the rates of revision hip arthroscopy and conversion to THA in order to identify risk factors for suboptimal outcomes. Methods: New York State Department of Health Statewide Planning and Research Cooperative Systems database was queried from 2011 through 2014 to identify patients undergoing hip arthroscopy. Patients were longitudinally followed for a minimum of two years to determine the incidence and nature of subsequent hip procedures. Multivariate logistic regression was performed to identify independent risk factors for revision surgery or conversion to THA. Results: We identified 3, 957 patients who underwent hip arthroscopy. Mean age of the sample was 35.8 years (SD±13.1). After a minimum follow-up of two years, overall failure rate was 9.6%: 3.7% (n=148) had revision hip arthroscopy at an average of 15.8 months, while 5.9% (n=235) converted to THA at 14.7 months. Index surgery performed by surgeons in the lowest volume tertile was an independent risk factor for both revision (p=0.001) and conversion to THA (p<0.001). Females (p<0.001), older patients (p<0.001) and those with a history of obesity (p<0.001) converted to THA at a significantly higher rate than other patients. Young patients (p<0.001) and females (p<0.001) were more likely to undergo revision hip arthroscopy. Conclusion: Hip arthroscopy may be better performed by medium to high volume surgeons. Additionally, patients with identified risk factors for revision or THA conversion should be counseled pre-operatively on potentially adverse outcomes, thus allowing patient-physician engagement during the shared decision-making process. Revision Hip Arthroscopy Risk Factor Odds Ratio (95% CI) Significance Age younger than 40 4.4 (1.8 - 18.0) p<0.001 Age between 40 - 50 3.4 (0.9 - 12.0) p=0.070 Age between 50 - 60 1.5 (0.3 - 6.1) p=0.246 Age greater than 60 Reference N/A Female Gender 1.6 (1.1 - 2.3) p=0.001 Absence of Labral Repair at Initial Hip Arthroscopy 1.75 (1.09 - 2.8) p=0.02 Initial Hip Arthroscopy by procedure in 3 rd Tertile 1.71 (1.1 - 2.8) p<0.001 Conversion to THA Risk Factor Odds Ratio (95% CI) Significance Age younger than 40 Reference N/A Age between 40 - 50 1.07 (0.28 - 1.38) p=0.620 Age between 50 - 60 1.03 (0.46 - 1.2) p=0.458 Age older than 60 1.8 (1.3 - 2.4) p=0.001 Female Gender 1.8 (1.3 - 2.4) p=0.001 Initial Hip Arthroscopy by procedure in 3 rd, Tertile 1.9 (1.2 - 2.8) p<0.001 Tobacco Use 1.9 (1.2 - 3.2) P<0.001 Obesity 5.6 (2.7 - 12.1) p<0.001 Osteoarthritis 2.4 (1.7 - 3.4) p<0.001